An evaluation of the children's literature collection in selected public libraries in Metro Manila - Samaniego, Carina C. (Institute of Library Science, University of the Philippines Diliman, 2001)
Literature is an important aid in helping children in their development. It can satisfy not only every child's informational needs, but his recreational and personal needs as well. Yet not every child has an equal opportunity to have access and enjoy their kind literature. Here the library, particularly the public library, has the role of providing a venue for children to enjoy the kind of literature suited to them.